Bimanual passive movement: functional activation and inter-regional coupling - Macaluso, Emiliano; Cherubini, Andrea; Sabatini, Umberto (Frontiers in Integrative Neuroscience, 2007)
The aim of this study was to investigate intra-regional activation and inter-regional connectivity during passive movement. During fMRI, a mechanic device was used to move the subject's index and middle fingers. We assessed four movement conditions (unimanual left/right, bimanual symmetric/asymmetric), plus Rest. A conventional intra-regional analysis identified the passive stimulation network, including motor cortex, primary and secondary somatosensory cortex, plus the cerebellum. The posterior (sensory) part of the sensory-motor activation around the central sulcus showed a significant modulation according to the symmetry of the bimanual movement, with greater activation for asymmetric compared to symmetric movements. A second set of fMRI analyses assessed condition-dependent changes of coupling between sensory-motor regions around the superior central sulcus and the rest of the brain. These analyses showed a high inter-regional covariation within the entire network activated by passive movement. However, the specific experimental conditions modulated these patterns of connectivity. Highest coupling was observed during the Rest condition, and the coupling between homologous sensory-motor regions around the left and right central sulcus was higher in bimanual than unimanual conditions. These findings demonstrate that passive movement can affect the connectivity within the sensory-motor network. We conclude that implicit detection of asymmetry during bimanual movement relies on associative somatosensory region in post-central areas, and that passive stimulation reduces the functional connectivity within the passive movement network. Our findings open the possibility to combine passive movement and inter-regional connectivity as a tool to investigate the functionality of the sensory-motor system in patients with very poor mobility.